Scaling CGIAR innovations with strategic partnerships - International Rice Research Institute (International Rice Research Institute, 2025)
This workshop convened CGIAR experts and partners from Southeast Asia to showcase agri-food system innovations and define scaling pathways, aiming to strategically align their work with country priorities and policies. Objectives included showcasing Asian Mega Deltas (AMD) accomplishments, providing an overview of CGIAR innovations in Southeast Asia to identify synergies for collaborative scaling, conducting practical exercises like innovation system analysis, and forming shared aspirations for scaling innovations with partners. The meeting was designed to facilitate a seamless transition into the next phase of science programs, leveraging AMD’s momentum and impact for sustainable and inclusive development. Expected outcomes included partners’ familiarity with AMD achievements, awareness of available CGIAR innovations mapped to policies or financial opportunities, selection of CGIAR innovation bundles and identification of scaling pathways, and increased coordination across Science Programs and centers in the region.